PENGARUH PENGGUNAAN GAMES INTERAKTIF KAHOOT! SEBAGAI MEDIA PEMBELAJARAN DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATA PELAJARAN IPS KELAS IV SDN BUAHGEDE - Dewi Komalasari, - (2022)
Dewi Komalasari. 2022. The Use Kahoot! Interactive Games As Learning Medium In Improving Students' Critical Thinking Skills. PGSD UPI Campus in Serang. In the era of development digital technology, technology can now be used in the world of education, one of which is used as technology-based learning media. In study researchers applied Kahoot! which can be used as learning media in social studies subjects to improve critical thinking skills of students in class IV at SDN Buahgede Serang-Banten with a total of 29 students. Because at SDN Buahgede application of technology in learning has not yet been implemented. Judging from the problems that researchers found at SDN Buahgede, researchers felt that there should be innovation from the teacher in classroom learning activities to foster critical thinking skills, one of which is in the learning media. So that students' critical thinking skills can develop. The learning media that will be applied by researchers is the Kahoot! application. Because the Kahoot! is an interactive quiz where it can measure students' insight into the material that has been given by the teacher. This study uses an experimental method with a research design of One Group Pretest-Posttest. With a quantitative approach where data processing uses the Wilcoxon Test which is carried out in the SPSS application. Initial conditions before the application of Kahoot! students' critical thinking skills have not been seen. This is evident from the average value of the class when answering the pretest was only 35.17. Furthermore, after doing the post-test, there was a good increase which was known to be the average value of the class to be 66.90. The results of the Wilcoxon test also obtained a sig value from the pretest and posttest, namely ,000, meaning that there was an increase in students' critical thinking skills in social studies subjects. It can be concluded that the application of Kahoot! become a learning media able to improve students' critical thinking skills.